Two cases of penetrating left ventricular cardiac trauma: Pre-hospital ultrasound and direct to theatre. (June 2019) - Hanley, Paul; Holden, Joshua; Johnson, Tamara; Garner, Alan; Weatherall, Andrew
Abstract: Left ventricular (LV) Cardiac penetrating trauma is a rare and grave injury. In cases of penetrating cardiac trauma, pre-hospital Ultrasound by flight doctors can assist identify specific pathology. This pre-hospital triage has now been linked to a change in both pre-hospital and in-hospital management. There are minimal cases reported where Pre-Hospital ultrasound provided definitive diagnosis and, while providing Pre-Hospital blood transfusion, informed a direct to theatre approach. In 2017 in New South Wales, Australia, a new protocol "Code Crimson" has been introduced to formalise a system wide process where Pre-Hospital medical teams can expedite a straight to Theatre approach.